Democracy, Credibility and Clientelism - Keefer, Philip (World Bank, Washington, DC, 2012)
The authors demonstrate that sharply different policy choices across democracies can be explained as a consequence of differences in the ability of political competitors to make credible pre-electoral commitments to voters. Politicians can overcome their credibility deficit in two ways. First, they can build reputations. This requires that they fulfill preconditions that in practice are costly: informing voters of their promises; tracking those promises; ensuring that voters turn out on election day. Alternatively, they can rely on intermediaries -- patrons - who are already able to make credible commitments to their clients. Endogenizing credibility in this way, the authors find that targeted transfers and corruption are higher and public good provision lower than in democracies in which political competitors can make credible pre-electoral promises. The authors also argue that in the absence of political credibility, political reliance on patrons enhances welfare in the short-run, in contrast to the traditional view that clientelism in politics is a source of significant policy distortion. However, in the long run reliance on patrons may undermine the emergence of credible political parties. The model helps to explain several puzzles. For example, public investment and corruption are higher in young democracies than old; and democratizing reforms succeeded remarkably in Victorian England, in contrast to the more difficult experiences of many democratizing countries, such as the Dominican Republic.